Asplenium nidus L. pada Beberapa Pohon Inang di Kawasan Taman Wisata Alam Bukit Kelam, Kabupaten Sintang, Kalimantan Barat - Mudiana, Deden (Universitas Atma Jaya Yogyakarta, 2008)
Asplenium nidus L. is one of epiphyte fern that commonly known by most people. This research aims to observe distribution pattern of Asplenium nidus that growth on host trees at Taman Wisata Alam Bukit Kelam. One hundred sixty Asplenium nidus have been observed grow on 66 individual host trees. Most of them grow on zone 4 (midle part of branches of three) on the host trees. Surface of bark on host trees and form of branches are environment factors that influence the growth of Asplenium nidus.